Visualization of electrographic flow fields of increasing complexity and detection of simulated sources during spontaneously persistent AF in an animal model - Kong, Melissa H.; Castellano, Steven; Ruppersberg, Peter; Lizama, Ken S.; Avitall, Boaz (Frontiers in Cardiovascular Medicine, 2023)
Background Mapping algorithms have thus far been unable to localize triggers that serve as drivers of AF, but electrographic flow (EGF) mapping provides an innovative method of estimating and visualizing in vivo, near real-time cardiac wavefront propagation. Materials and Methods One-minute unipolar EGMs were recorded in the right atrium (RA) from a 64-electrode basket catheter to generate EGF maps during atrial rhythms of increasing complexity. They were obtained from 3 normal, animals in sinus rhythm (SR) and from 6 animals in which persistent AF which was induced by rapid atrial pacing. Concurrent EGF maps and high-resolution bipolar EGMs at the location of all EGF-identified sources were acquired. Pacing was subsequently conducted to create focal drivers of AF, and the accuracy of source detection at the pacing site was assessed during subthreshold, threshold and high-output pacing in the ipsilateral or contralateral atria (n = 78). Results EGF recordings showed strong coherent flow emanating from the sinus node in SR that changed direction during pacing and were blocked by ablation lesions. Additional passive rotational phenomena and lower activity sources were visualized in atrial flutter (AFL) and AF. During the AF recordings, source activity was not found to be correlated to dominant frequency or f wave amplitude observed in concurrently recorded EGMs. While pacing in AF, subthreshold pacing did not affect map properties but pacing at or above threshold created active sources that could be accurately localized without any spurious detection in 95% of cases of ipsilateral mapping when the basket covered the pacing source. Discussion EGF mapping can be used to visualize flow patterns and accurately identify sources of AF in an animal model. Source activity was not correlated to spectral properties of f-waves in concurrently obtained EGMs. The locations of sources could be pinpointed with high precision, suggesting that they may serve as prime targets for focal ablations.